The roles of radio stations in disseminating news information towards university students in Rembau / Adam Afifi Rishinsa - Rishinsa, Adam Afifi (2017)
This paper studies the role of radio stations on how they disseminate news information towards university students in Rembau. The paper starts by explaining the history of radio up the 2nd World War and also how radio got its start in Malaysia. Radio is not without its limitations. This paper discovers how hard it is to understand the messages on radio as it has no visuals, how the short life span of messages on radio can affect listener experience and the media preferences of the university students in Rembau. Questionnaires are given to university students in Rembau and the analysis of this paper would be derived from there. It is concluded that it is not hard to understand messages on the radio even though there is no visual aid; the short life span of messages on the radio can be tackled with various means and university students in Rembau thinks that radio is still relevant even though they prefer online media.